Pengaruh Media Iklan Advertorial terhadap Kemampuan Menulis Teks Persuasif oleh Siswa Kelas VIII MTs Muhammadiyah 22 Padangsidimpuan. - Nur Afifah (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
This study aims to: 1) To determine the effect of advertorial advertising media; 2) To determine the students' ability to write persuasive texts; 3) To determine the effect of advertorial advertising media on students' ability to write persuasive texts. The type of research used in this study is a quantitative type. The sample used was 26 students. data collection techniques using tests and then analyzed using descriptive statistics. The results showed that the alternative hypothesis upheld in this study was acceptable. That is, there is a significant relationship between the influence of advertorial advertising media on the ability to write persuasive texts by class VIII Mts. Muhammadiyah 22 Padangsidimpuan. This can be seen from the value of the variable X obtained 1890, the variable Y obtained 1820 and the price "r" obtained from the calculation of the product moment correlation of 0.423 categorized as "fair/moderate".Keywords: Advertorials, writing skills, persuasive text